Sociometric Status at Classroom’s Context: Role of Emotional Intelligence - Bhoumick, Proloyendu (Voices of Teachers and Teacher Educators, 2023)
Emotional Intelligence refers to the ability to identify, understand, manage, and effectively use one’s own emotions and emotions of others. It helps the students to be better performers in school, team activities, and conflict resolutions and many more. On the other hand, sociometric status of a student is determined by the extent to which they are liked or disliked by the peers. The present study has shed light on the association between the levels of Emotional Intelligence (High, Average, and Low) of the students and their Sociometric statuses (Preferred, Rejected, Neglected, Controversial and Average) in the classroom’s context. A total of 178 students of Class IX from 4 conveniently selected classrooms participated in this study. They completed the ‘BASPBEIT-Emotional Intelligence test’ first before they gave the three names of the peers from their respective classrooms “whom they liked most” and “whom they liked least” in a blank sheet. A chi-square test of independence was used to examine this association. A “low to moderate”association was found between the Emotional Intelligence and Sociometric Status. Results also revealed that the sociometrically Preferred students have High Level of Emotional Intelligence in comparison with the students of other sociometric statuses. The sociometrically Rejected students have Low level of Emotional Intelligence. Sociometrically Neglected students are more associated with the Average Level of Emotional Intelligence. The other two sociometric statuses are not significantly associated with any levels of Emotional Intelligence.